The First Look in Autism Spectrum Disorder (ASD) Geographical Distribution in National Reference Hospital, South Sumatera Region, Indonesia - Ziske Maritska; Bintang Arroyantri Prananjaya; Nita Parisa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Background. Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition characterized with disorders in cognitive, behaviour, and social interaction. It is estimated to affect 1:160 children worlwide. Despite its increasing trend, the exact cause of it is yet to be known. Objective. This study wished to identify the geographical distribution of ASD cases in Dr. Mohammad Hoesin Hospital as one of the national reference hospitals in Indonesia for South Sumatera region. Methods. Medical records of the patients who are diagnosed with ASD during 2014-2018 was observed in order to identify the patients’ residential area. Results. There were 107 patients who were clinically diagnosed of having ASD during 2014-2018 in Dr Mohammad Hoesin Hospital, Palembang. Based on its residential area, ASD cases were mostly found in Palembang as the capital city of South Sumatera Province. Conclusion. ASD is found in small and big cities across the South Sumatera province, implying its common occurrence. The varied prevalence could be signifying the role of different related risk factors identified in the area.